2005
DOI: 10.1007/s11205-004-0562-y
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship Between Personality, Supportive Transactions and Support Satisfaction, and Mental Health of Patients with Early Rheumatoid Arthritis. Results from the Dutch Part of the Euridiss Study

Abstract: The relationship between personality, supportive transactions and support satisfaction, and mental health of patients with early rheumatoid arthritis. Results from the Dutch part of the Euridiss study Suurmeijer, TPBM; van Sonderen, Frideric; Krol, B; Doeglas, DM; van den Heuvel, Wilhelmus; Sanderman, Robbert Take-down policy If you believe that this document breaches copyright please contact us providing details, and we will remove access to the work immediately and investigate your claim.Downloaded from the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
14
0
1

Year Published

2006
2006
2018
2018

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 24 publications
(17 citation statements)
references
References 29 publications
2
14
0
1
Order By: Relevance
“…Extraversion, agreeableness, and conscientiousness positively affect life satisfaction via more active problem solving, less depressive coping, and/or more active search for social support. This conforms to previous studies that found the effects of neuroticism and extraversion to be mediated by coping [14,15] and extends this knowledge to two more Big 5 personality traits. Only for openness for experience no mediating effects could be found, probably pointing to the somewhat different nature of this personality dimension [21].…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…Extraversion, agreeableness, and conscientiousness positively affect life satisfaction via more active problem solving, less depressive coping, and/or more active search for social support. This conforms to previous studies that found the effects of neuroticism and extraversion to be mediated by coping [14,15] and extends this knowledge to two more Big 5 personality traits. Only for openness for experience no mediating effects could be found, probably pointing to the somewhat different nature of this personality dimension [21].…”
Section: Discussionsupporting
confidence: 91%
“…All Big 5 personality traits and nearly all coping strategies showed univariate associations with life satisfaction. With regard to personality, the results are in line with previous studies investigating neuroticism and extraversion in patients with rheumatic diseases [13][14][15], and with the assumption that openness to experience, agreeableness, and conscientiousness are also related to adjustment to rheumatic diseases. Turning to coping, the findings support previous research in patients with rheumatic diseases [10][11][12] and emphasize the relevance of coping in adjustment to rheumatic diseases.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…Nevertheless, it must be emphasized that social support is a multi-dimensional phenomenon and a number of studies have explored its facets and its specific functions [7,14,26]. Furthermore, an important distinction has to be made in cases where social support can be addressed either as a structure reflecting one's rootedness in the social system or from a functional point of view [27].…”
Section: Research Papermentioning
confidence: 99%